Characterization of nutritional status and eating habits of children from the 2nd and the 3rd years of elementary school. (29th March 2019) - de Sousa, Inês; Lopes, Anabela; Friães, Paula; Ramalho, Renata; Pereira, Paula
Abstract : Introduction: According to the Direção Geral da Saúde, the practice of healthy eating plays an important role in the development and growth of children, as well as in the preservation of their health [1 ]. Thus, the main objective of the present study was to characterize the nutritional status and eating habits of students in the 2nd and in the 3rd years of elementary school. Material and methods: The study sample consisted of 59 students from the 2nd and the 3rd years of elementary school. Nutritional status was assessed by collecting the anthropometric data (weight and height), with the informed consent of the parents, and eating habits were assessed through a food questionnaire. Nutritional status assessment was performed according to WHO criteria. Results: Data on nutritional status showed that most children (56%, n = 33) presented normal nutritional status, 35% (n = 20) presented overweight (25% obesity and 10% pre-obesity) and 10% (n = 6) presented a state of thinness. Regarding the number of meals, 83% (n = 49) of the students reported to have four to six meals a day. Regarding breakfast, 48% (n = 24) had a preference for plain milk, being the preferred solid foods breakfast cereals (28%, n = 14) and bread (28%, n = 14). As for the most consumed foods in morning and afternoon snacks, bread (51%, n = 26) and cookies (21%, n = 10) were first choices. The most commonly consumed liquid foods were soft drinks (29%, n = 14), milk with chocolate (20%, n = 10) and plain milk (19%, n = 10). Most students (81% at lunch and 90% at dinner) reported that they had not eaten soup the day before in both main meals. The same was true for the consumption of vegetables on the plate, in which the majority of the students both at lunch (92%) and at dinner (85%) reported not having eaten the day before. For beverages consumed at main meals, soft drinks were students' preferred beverages (40% at lunch and 43% at dinner). On the previous day, most students (56%, n = 33) reported not having consumed fruit, 32% (n = 19) reported having consumed a piece of fruit, 9% (n = 5) two pieces of fruit, and only 3% (n = 2) reported having ingested three pieces of fruit. Discussion and conclusions: Dietary habits of studied children show a daily consumption of sugary enriched foods (soft drinks, cereals, biscuits) and a low consumption of soup, vegetables and fruit. It is therefore necessary to focus on the promotion of healthy eating habits among children in order to prevent the appearance of chronic noncommunicable diseases.